Team O2AC at the world robot summit 2020: towards jigless, high-precision assembly. (17th November 2022) - von Drigalski, Felix; Beltran-Hernandez, Cristian C.; Nakashima, Chisato; Hu, Zhengtao; Akizuki, Shuichi; Ueshiba, Toshio; Hashimoto, Manabu; Kasaura, Kazumi; Domae, Yukiyasu; Wan, Weiwei; Harada, Kensuke
Abstract : High-mix, low-volume assembly has been a long-standing challenge for robot systems. We present a complete 2-armed robot system with general-purpose grippers and hand-held tools, which can perform assembly for a wide variety of objects with tight tolerances. The complete source code and 3D-printed-part designs are available for download and can be executed in simulation and with physical robots using a regular desktop computer. Furthermore, we present the designs of multiple tools which can be grasped and used by the robots in a human-like fashion. The system uses no parts-specific jigs and grippers to be applied to many different parts. It achieves high precision and reliability by using the environment and gripper surfaces to position the grasped objects. The system obtained 3rd place and the Japanese Society for Artificial Intelligence Award at the World Robot Summit 2020 Assembly Challenge. GRAPHICAL ABSTRACT: UF0001